How to ‘legally' decimate Jews? Directives on residence restrictions in the general government – considerations on legal regulations and practice - Bartnicka, Alicja (Holocaust studies, 2025)
The aim of this article is a theoretical and practical analysis of directives on residence restrictions in the General Government directed toward the Jewish population, the final effect being the third ordinance that legitimized the death penalty (regulation of October 15, 1941). During the research, we tried not only to characterize the activity of special courts (Sondergerichte) that applied these directives in the GG. Our goal was also to point out problems with the interpretation of these provisions and to describe executions ruled by the judges in special courts. We have also investigated selected cases of Jews who were arrested and sent to death without a ruling of capital punishment for breaching the regulations in question, as well as the approach of judges and prosecutors toward the laws applicable at the time.